Evaluation and Uptake of an Online ADHD Psychoeducation Training for Primary Care Health Care Professionals: Implementation Study - Blandine French; Hannah Wright; David Daley; Elvira Perez Vallejos; Kapil Sayal; Charlotte L Hall (JMIR Medical Education)
Abstract BackgroundHealth care professionals seldom receive training on neurodevelopmental conditions such as attention-deficit/hyperactivity disorder (ADHD). An online training was co-developed to address some of the gaps in knowledge and understanding in primary care. A randomized controlled trial demonstrated that the training increased knowledge and confidence and improved practice. ObjectiveThis report highlights the implementation of the training in practice and follow-up 4 years post evaluation. MethodsThe online ADHD training comprises 2 modules: “Understanding ADHD” and “The Role of the GP,” each taking approximately 45 minutes to complete. The training targets general practitioners primarily but is open to other health care professionals and parents. Feedback was collected through a survey at the end of the training, and the training has been widely adopted by various organizations internationally and nationally. ResultsBetween December 2019 and January 2024, the “Understanding ADHD” module was accessed more than 13,486 times, while the “Role of the GP” module was accessed 7018 times, primarily by users from the United States and the United Kingdom. Survey results from both modules showed positive feedback with high ratings for usefulness, likelihood to inform practice, and recommendation to colleagues. Some suggestions for improvement included reducing the negative focus on ADHD consequences and incorporating more positive aspects of ADHD. ConclusionsThis ADHD online training program, despite facing implementation challenges, has seen positive outcomes, including international translation and high user ratings. Suggestions for improvement were received, but some were not feasible due to regional variations in ADHD pathways. The training’s impact extended beyond GPs to other health care professionals, although the COVID-19 pandemic posed obstacles to dissemination efforts. Nonetheless, ongoing plans aim to expand the training’s implementation globally.